Dyeing of Wool Fibres with Synthetic Dyes and Effect of Proteolytic Enzymes - DOGRU, MEHMET; AYTEKIN, CETIN (Asian Journal of Chemistry, 2010)
In spite of protein and protein fragments (casein, peptone, etc.) are used widespread as a substrate for the proteolytic enzymes, the substrate prepared from dyes that adsorbed on appropriate material, such as wool and cotton are also used for enzymes activity determination. The object of this work is to develop the substrates which are easily and economically obtainable and also environmental safer, for the frequently used proteolytic enzymes such as subtilisin carlsberg, trypsin, chymotrypsin and protease type XVI and if it is possible to prepare the specific substrate at least for one of this enzymes. For this aim, wool was dyed with synthetic dyes such as procion yellow, procion red and procion blue. The results indicate that the most appropriate complex was found to be woolprocion yellow and the most unappropriate complex was found to be wool-procion blue complex.